New Guidelines of Pediatric Cardiac Implantable Electronic Devices: What Is Changing in Clinical Practice? - Massimo Stefano Silvetti; Diego Colonna; Fulvio Gabbarini; Giulio Porcedda; Alessandro Rimini; Antonio D’Onofrio; Loira Leoni (Journal of Cardiovascular Development and Disease, 2024)
Guidelines are important tools to guide the diagnosis and treatment of patients to improve the decision-making process of health professionals. They are periodically updated according to new evidence. Four new Guidelines in 2021, 2022 and 2023 referred to pediatric pacing and defibrillation. There are some relevant changes in permanent pacing. In patients with atrioventricular block, the heart rate limit in which pacemaker implantation is recommended was decreased to reduce too-early device implantation. However, it was underlined that the heart rate criterion is not absolute, as signs or symptoms of hemodynamically not tolerated bradycardia may even occur at higher rates. In sinus node dysfunction, symptomatic bradycardia is the most relevant recommendation for pacing. Physiological pacing is increasingly used and recommended when the amount of ventricular pacing is presumed to be high. New recommendations suggest that loop recorders may guide the management of inherited arrhythmia syndromes and may be useful for severe but not frequent palpitations. Regarding defibrillator implantation, the main changes are in primary prevention recommendations. In hypertrophic cardiomyopathy, pediatric risk calculators have been included in the Guidelines. In dilated cardiomyopathy, due to the rarity of sudden cardiac death in pediatric age, low ejection fraction criteria were demoted to class II. In long QT syndrome, new criteria included severely prolonged QTc with different limits according to genotype, and some specific mutations. In arrhythmogenic cardiomyopathy, hemodynamically tolerated ventricular tachycardia and arrhythmic syncope were downgraded to class II recommendation. In conclusion, these new Guidelines aim to assess all aspects of cardiac implantable electronic devices and improve treatment strategies.